Pengaruh Literasi Digital dan Media Youtube Terhadap Hasil Belajar Kimia - Hadori Hadori (Jurnal Ilmiah Wahana Pendidikan, 2022)
Abstract: The purpose of this study was to determine the effect of digital literacy and youtube media on chemistry learning outcomes. This research method is quantitative, the instrument used is a questionnaire. Population and sample of students of SMKN 1 Pulo Ampel class X all majors in the academic year 2021/2022 Odd, 80 students selected randomly as a sample. Data collection was carried out by distributing questionnaires and questionnaires. Data analysis with descriptive statistical methods, and multiple regression analysis. The results showed that there was an influence of digital literacy (X1) and youtube media (X2) on the learning outcomes of Chemistry (Y), this is evidenced by the regression calculation which shows the calculated F value > F table or 35.208 > 3.11 with the regression equation = -1.028 +0.597X1 +0.643X2. Furthermore, digital literacy variables and youtube media together can determine student learning outcomes 47.8% and are significant. Keyword: Digital literacy, Youtube media, Chemistry learning outcome